Policy based management for dynamic organisations - Feeney, Kevin Chekov (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2009)
Policy-Based Management (PBM) is a recent development in systems and network management research which aims to address the challenge of efficiently managing complex and heterogeneous information systems. Broadly speaking, the goal of policy based management is to enable information systems to be adaptive and to dynamically change their behaviour during operation in order to reflect the high-level business goals of the organisation. Although current PBM systems contain elements of an organisational model, their support for highly-dynamic organisations and devolved decision making is limited. This thesis proposes the Community Based Policy Management System (CBPMS), a system consisting of a formal model of the organisation, a clear definition of its state transitions and a service oriented architecture for deployment.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.